TINGKAT KOROSIFITAS AIR DI PERAIRAN PEMBANGKIT LISTRIK AIR WADUK CIRATA - Dadan Sumiarsa; Yayat Dhahiyat; Sunardi Sunardi Sunardi (JURNAL ISTEK, 2011)
Corrosive water will affect the age of dam and hydroelectric equipment, hydropower. Analysis of water quality parameters of physical-chemistry at the surface and depth at the dam site and hydropower intake Cirata. Results of analysis using water corrosion index shows that the value of LSI 6.0 ie, 8.9 s / d 10.5 and LI> 0.2 0.63-0 , 97. Index value indicates the water in the water for hydropower generation Cirata (Dam site and Intake) has corrosive tendencies.